미디어스포츠의 언어적 이미지 분석 - 조성식; Seong Sik Cho; 김종; Chong Kim; 한동섭; Dong Sub Han; 김성훈; Sung Hun Kim (Ch'eyuk kwahak yŏn'gu, 2009)
이 연구에서는 `어휘`를 이용하여 미디어에 의해 매개된 스포츠의 이미지를 언어적으로 구체화하여 미디어 스포츠콘텐츠의 이미지적 가치를 분석하고자 하였다. 미디어 스포츠콘텐츠의 이미지상의 구체화는 세 단계에 의해 이루어졌다. 첫 번째 단계는 이미지 스케일에 사용될 연구대상별 이미지 형용사(서술적 동사포함)의 풀(pool)을 찾아내는 단계로 대학생의 시각에서 자유연상법을 이용하여 자유롭게 연구대상물에 대한 형용사 이미지를 적도록 유도하는 방법을 사용하였다. 두 번째 단계는 대표성 있는 단어를 추출하는 단계로 설문 문항을 통해 단어 풀을 제시하고 리커트 5점 척도를 통해 답변하게 한 후 자료를 수집하였다. 마지막으로, 수집된 데이터는 기술통계분석과 요인분석을 실시하였다. 미디어에 의해 중재된 스포츠는 ① 동적 이미지 ② 자극적이미지 ③ 진취적이미지 ④ 미적이미지 ⑤ 상업적이미지 ⑥ 귀족적이미지 ⑦ 사실적이미지를 떠올리는 것으로 나타났으며 자극적이미지, 귀족적이미지, 미적이미지가 상대적으로 높게 수용자에게 그려지고 있는 것으로 나타났다. This study attempted to figure out which images are expressed in sport contents presented through the media in order to explore the image values of media sport contents. Three procedures were adopted to draw the verbal images of sport contents in the media. The first step was to find out the pool of verbal expression to be associated with sport contents and to use the methods of image association for college students to freely write down their words from image association and impression about sport contents in the media. The second step was to gather the typical and representative words from subjects` image association from media sport contents. And such words were evaluated with 5 point Likert scales. The last step was to analyze the collected data with the descriptive statistics and factor analysis. The result showed that the media sport contents have 7 different images including dynamic, stimulated, aesthetic, commercial, noble, and realistic images. The dynamic images were diversely expressed and the stimulated altruistic, and aesthetic images were highly received, as compared to the other images.